The seven faith tribes : who they are, what they believe, and why they matter - Barna, George (Carol Stream, Ill. : BarnaBooks/Tyndale House Publishers, 2009)
George Barna identifies, describes, and analyzes seven major "faith tribes" (Captive Christians, Casual Christians, Jews, Mormons, Pantheists, Muslims, and Skeptics) in America--documenting who they are, what they believe, how they vote, and what they are passionate about. --from publisher description.
America is on the path to self-destruction -- Casual Christians -- Captive Christians -- American Jews -- The Mormon expansion -- Pantheists: people of different gods -- Muslims in America -- Spiritual skeptics -- Calibrating our values and worldview -- Empowering values-driven leaders -- Recommissioning the media -- Stepping up the family's contribution -- Faith tribes must pull their weight -- A vision for restoring America -- A summary of common worldviews held by Americans -- Selected survey data comparisons across tribes -- America's shared values -- Description of the research methods.
Includes bibliographical references (pages 229-233).
Keywords: United States -- Religion -- 1960-; Values -- United States; Religion; Since 1960